2013 IEEE Global Communications Conference (GLOBECOM) 2013
DOI: 10.1109/glocom.2013.6831694
|View full text |Cite
|
Sign up to set email alerts
|

Azimuth and elevation sectorization for the stadium environment

Abstract: The stadium environment represents one of the tougher environments for cellular systems given the extreme density of users and the potential for a large amount of uplink traffic. This paper presents the design and evaluation of 2D antenna arrays employed with azimuth and elevation sectorization in the stadium environment to improve the 3GPP LTE mobile network performance. A typical stadium model is introduced and different deployment options for a 2D antenna array with multiple sector beams are considered. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Moreover, such a placement mitigates human blockage losses [6], [8]. Regarding the orientation of the transmitting antennas, the main approach is to direct the main beam of the antenna to the center of its sector [11], [15].…”
Section: B Ap Placementmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, such a placement mitigates human blockage losses [6], [8]. Regarding the orientation of the transmitting antennas, the main approach is to direct the main beam of the antenna to the center of its sector [11], [15].…”
Section: B Ap Placementmentioning
confidence: 99%
“…Most existing work focuses on specific antenna patterns. Useful comparisons between narrow-and broad-beamwidth antennas were made in [11]- [13], [15]. It was found that the directive (narrow-beamwidth) antennas offered better signalto-noise and interference levels at high-density AP deployments (124 and 344 APs), compared to broader-beamwidth antennas.…”
Section: Antenna Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…This array balances the flexibility and gain of full-dimensional beamforming with the simplicity and efficiency of more traditional arrays. Operators have traditionally preferred sectorization and tilt control as a means of beamforming [41], [42], so we limit the investigation to one-dimensional geometry. We leave the evaluation of twodimensional arrays to future work.…”
Section: B Multicell System Configurationmentioning
confidence: 99%
“…Taking into account the first challenge inherent to future wireless communication, in [2], the authors investigated several stationarity properties of a massive multiple input and multiple output (MIMO) channel in a stadium at 1.4 and 4.4 GHz. Also, in [3] the design of twodimensional (2D) arrays in a stadium was considered for increasing the capacity through large cell sectorization. Regarding the second challenge, measurements and research have been conducted in stadiums in order to analyze the coverage and capacity at 28 and 5 GHz, considering body loss as parameter that can severely affect system performance [4]- [6].…”
Section: Introductionmentioning
confidence: 99%